A corny cause of cerebrospinal fluid ascites: A case report and review of literature. (26th July 2016) - Jamal, Hira; Abrams, Gary
Objective: To report a rare cause of cerebrospinal fluid ascites. Methods: A 37-year-old female with history of intracranial hypertension and a ventriculo-peritoneal shunt was referred to liver clinic for evaluation of newly developed ascites. Results: Initially, the cause of ascites was thought to be secondary to a liver etiology. However, this was excluded after a comprehensive evaluation including portal pressure measurements. We determined the ascites to be infected cerebrospinal fluid secondary to a rare commensal organism, Corynebacterium non-Jeikeium, which resolved after removing ventriculo-peritoneal shunt, appropriate antibiotics and conversion to a ventriculo-atrial shunt. Conclusion: Cerebrospinal fluid ascites is a rare complication of VP shunts and since 1976 only 8 cases of Corynebacterium non jk VP shunt infections have been reported in the literature but none associated with ascites. Also this report highlights the beneficial role of transjugular portal pressure measurements in the evaluation of ascites.